Immunisation and pregnancy - who, what, when and why? - Wiley, K.; Regan, Annette; McIntyre, P. (National Prescribing Service Ltd., 2017)
Only two vaccines are routinely recommended during pregnancy - influenza vaccine is recommended throughout, and pertussis vaccine is recommended at 28-32 weeks but can be given later. Some other vaccines can be administered in special circumstances but are not routinely recommended. All live attenuated vaccines are contraindicated in pregnancy, although there has been no evidence of adverse effects from inadvertent administration. Recommending vaccination to pregnant women is important as evidence shows they are more likely to get vaccinated if their healthcare provider advises it. It is important for healthcare providers to discuss the benefits and the safety of vaccination during pregnancy. In particular, pointing out the benefits for the baby is important in helping women decide.